AB1280 Diurnal variation of power doppler signal in metacarpophalangeal joints of patients with rheumatoid arthritis. (23rd January 2014) - Semerano, L.; Gutierrez, M.; Ariani, A.; Falgarone, G.; Filippucci, E.; Saidenberg-Kermanac'h, N.; Boissier, M.-C.; Grassi, W.
Abstract : Background: In a preliminary study on 10 patients with active rheumatoid arthritis (RA) we could show for the first time that Power Doppler ultrasonography (PDUS) signal of metacarpophalangeal (MCP) joints has a clear diurnal variation, being higher in the morning vs. early afternoon and evening. We extended our study and involved a total of 36 patients with active RA in order to confirm our preliminary results Objectives: To test, in a larger series, whether PDUS signal of MCP joints in RA patients varies according to the time of day Methods: A total of 360 MCP joints from 36 patients with active RA (DAS28>3, 2) were evaluated for both presence-absence of PDUS signal and according to a semiquantitative score at three different times of day T0: between 7 and 10 a.m.; T1: 4-6 hours after T0; T2: 4-6 hours after T1. The scores at T0, T1 and T2 were compared for each joint. Before each PDUS examination the patient filled out a 100 mm visual scale of pain (VAS). The day of PDUS assessment, factors that could potentially influence PDUS signal or VAS results were minimized. All patients seated in a temperature-controlled room for at least 30 minutes before PDUS examination to stabilize the blood flow. They avoided smoke, alcohol, corticosteroids, NSAIDs, analgesics and vasoactive drugs intake. Room temperature was kept stable. For PDUS examination patients put their hands inside a silhouette drawn on the paper sheet lying on the bench to avoid any change in hands' position across the three examinations. Results: PDUS presence/absence: there was a significant variation in the number of positive MCP joints during the day (p=0.01). There were more PDUS positive MCP joints at T0 (109) vs. T1 (97) (p<0.05) and vs.T2 (93) (p<0.05). Semiquantitative PDUS scores were significantly higher at T1 (mean rank 2.19) with a subsequent reduction at T2 (mean rank 1.93) (p<0, 05) and at T3 (mean rank 1.88) (p<0, 05). PDUS scores correlated with pain visual scale values at T0, T1 and T2 (rho 0, 54; p<0, 001). All patients displayed some sort of circadian variation, and the vast majority had higher scores at T1, nevertheless some patients (3) had higher scores at T2 or T3. Conclusions: Diurnal variation of PDUS signal of MCP joints is a feature of patients with active RA and correlates with joint pain. The vast majority of patients displays higher PDUS signal in the morning compared to afternoon and evening, but some selected patients may have a different circadian variation, with higher signal later during the day. Disclosure of Interest: None Declared